2021
DOI: 10.3389/fmed.2020.627617
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Evoked Itch in Human Subjects

Abstract: Administration of chemicals (pruritogens) into the skin evokes itch based on signal transduction mechanisms that generate action potentials mainly in mechanically sensitive and insensitive primary afferent C-fibers (pruriceptors). These signals from peripheral neurons are processed in spinal and supra-spinal centers of the central nervous system and finally generate the sensation of itch. Compared to chemical stimulation, electrical activation of pruriceptors would allow for better temporal control and thereby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 85 publications
(129 reference statements)
0
8
0
Order By: Relevance
“…No matter which of the transmission theories for itch proves ultimately true, itch, like pain (Fillingim, 2017 ), exhibits large interindividual variability, as observed with human subjects and atopic dermatitis patients: in this study, individual differences in skin pathophysiology and psychological state were suggested as possible reasons for the observed differences (Solinski and Rukwied, 2020 ). Further examples are provided based on the side effects of specific drugs.…”
Section: Introductionmentioning
confidence: 67%
“…No matter which of the transmission theories for itch proves ultimately true, itch, like pain (Fillingim, 2017 ), exhibits large interindividual variability, as observed with human subjects and atopic dermatitis patients: in this study, individual differences in skin pathophysiology and psychological state were suggested as possible reasons for the observed differences (Solinski and Rukwied, 2020 ). Further examples are provided based on the side effects of specific drugs.…”
Section: Introductionmentioning
confidence: 67%
“…Other studies have evoked cutaneous itch electrically and thereby gained better temporal control on pruritus generation without allergen sensitization or dependence on chemical pathways ( Solinski and Rukwied, 2020 ). However, this mechanism without pruritogen receptor activation is perhaps best suited to observe brain activity patterns and to identify regions involved in itch processing.…”
Section: State Of the Art In Itch Researchmentioning
confidence: 99%
“…1 In this process, the neurosensory signal is conducted by primary afferent fibers (pruriceptors) from the skin chemical (e.g., pH), physical (e.g., temperature, tissue tension), and cellular (e.g., lymphocytes, macrophages) environmental conditions. [6][7][8] Of particular interest is the influence of pruriceptors and thermosensitive nociceptors on sensory neurons (thermoceptors). The latter include both cold (activity <35 • C) and heat (activity >25 • C/>35 • C) receptors.…”
Section: Introductionmentioning
confidence: 99%
“…These pseudounipolar and polymodal pruriceptors are divided according to biophysical criteria into thin myelinated A (diameter 2–5 μm, conduction velocity < 8 m/s) and unmyelinated C fibers (diameter 0.2–1.5 μm, conduction velocity < 2 m/s) 4,5 . They are integrated into an interactive milieu that is regulated and determined by molecular (e.g., cytokines, ion channels), chemical (e.g., pH), physical (e.g., temperature, tissue tension), and cellular (e.g., lymphocytes, macrophages) environmental conditions 6–8 . Of particular interest is the influence of pruriceptors and thermosensitive nociceptors on sensory neurons (thermoceptors).…”
Section: Introductionmentioning
confidence: 99%